Sosialisasi dan FGD Penanggulangan Perdagangan Orang pada Masyarakat Raman Utara Kabupaten Lampung Timur - Mashuril Anwar; Maroni Maroni; Erna Dewi; Rini Fathonah (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2020)
In general, the people of North Raman District do not yet know and understand correctly about tackling trafficking. The people of North Raman Subdistrict have never received legal counsel regarding the crime of trafficking. Therefore, it is necessary to provide good knowledge and understanding through socialization and focus group discussions (FGD) to overcome the problems of partners related to the handling of trafficking in people in the North Raman Regency, East Lampung Regency. Efforts made in this activity are by providing knowledge and understanding of the law about tackling trafficking in people in the District of North Raman, East Lampung Regency. Then proceed with discussion and question and answer, and test the understanding of participants by giving a pre test and post test. The results of the activities show that the socialization activities and focus group discussions (FGD) are important to be carried out in order to increase knowledge, understanding and awareness of the legal community regarding tackling trafficking. How to cite:Anwar, M., Maroni, M., Dewi, E., Fathonah, R. (2020). Sosialisasi dan FGD Penanggulangan Perdagangan Orang pada Masyarakat Raman Utara Kabupaten Lampung Timur. Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 5(1), 53-59.DOI: https://doi.org/10.26905/abdimas.v5i1.3367